Perception of ACIS students towards the implementation of welfare state concept (Negeri Berkebajikan) in Kelantan / Nur Syakirah Mohamed - Mohamed, Nur Syakirah (Academy of Contemporary Islamic Studies, 2018)
Generally, education can be consider an important part of the welfare state. Education is one of the major agendas that can influence the life and quality civilization of a nation in the world. Humans will be considered backward if they do not have education. Knowledgeable individuals and families and putting knowledge as a way of life will assist us to make the right decision. This paper present about the perception of ACIS students towards the implementation of welfare state concept (Negeri Berkebajikan) in Kelantan. The main purpose of this study to examine the perception of students whether have the information on the implementation of welfare state concept in Kelantan. The main objective in this research is to examine the knowledge and awareness of the respondents about the Welfare State Concept (Negeri Berkebajikan) implemented in Kelantan. Secondly, to evaluate on the perception towards the importance of Welfare State Concept (Negeri Berkebajikan) in education and thirdly is to identify the problems and challenges in implementing the Welfare State Concept (Negeri Berkebajikan) from educational perspective. This research focused on the welfare state concept in educational perspective. The data were qunatitavely collected in nature because the researcher using the questionnaire survey form as instrument. The researcher use the non-probability sampling which is selected the purposive sampling where the respondent was purposely selected from Academy of Contemporary Islamic Studies (ACIS), Uitm Shah Alam. The findings of this research knows that most the respondents have knowledge about the implementation of welfare state concept (Negeri Berkebajikan). They also realize on the importance of welfare state concept (Negeri Berkebajikan) in education and needs to be maintained and improved in the future. The most of respondents agree that lack of information about welfare state concept (Negeri Berkebajikan) is one cause of problems and challenges in implementing of welfare state concept (Negeri Berkebajikan). Furthermore, the recommendations from researcher are firstly, is enhance the disclosure of information whereby the government of Kelantan need to enhance the disclosure of information about welfare state concept. Secondly, is cooperation between leaders and society is very important because this task is a collective responsibility. The conclusion is welfare state concept (Negeri Berkebajikan) is very important to all people. Based on al- Quran, Allah SWT has told all Muslims to always help each other. In order to fulfill the concept of charity which will benefit all. So concept also is a responsibility for all people including leader and community as each party should collaborate and play their roles together to realize the aim of welfare state concept (Negeri Berkebajikan) from the Islamic perspective.